Study of the effectiveness of the traditional system of training 6-10-years-old involved in football - Maksymenko, I.G.; Samer, Majed Dmor (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose : to identify the degree of efficiency traditionally used in Ukraine, the organization and conduct classes on football with students 6 to 10 years. Material : the study involved 57 students, ages 6-10 years. Investigations were carried out through the use of Polar Team System. Results : the indexes of the pulse energy and the cost of various options for training sessions, traditionally held in the sections with the children in groups of initial training. Marked reaction parameters organism beginners to competitive load. Substantiated quantitative characteristics of the diet of children. The data of the comparative analysis of energy cost of training sessions and daily food intake of children. Conclusions : It was found that classes with beginners accompanied by the use of heavy loads, often diet does not provide full recovery in children.